Teachers’ Perception of the Influence of the Teaching Context on Cognitive Achievements in General Technology Education - Damir Purković; Stjepan Kovačević (International Journal of Cognitive Research in Science, Engineering and Education, 2020)
High achievements in the cognitive domain are the ultimate goal of any education, within it is important to understand the role of the teaching context. In this regard, the purpose of this research was to determine how teachers perceive the role of the teaching context on the pupils’ achievements in the cognitive domain in general technology education. For this purpose, a survey of teachers’ perception towards the influence of isolated elements of the teaching context, specific to technology education, on the achievements of learning objectives was conducted. The study was conducted as a survey on a stratified sample of technology education teachers (N = 194) from Croatia. ANOVA repeated measurements statistical procedure was used to process the research results. The analysis of the results showed that teachers give preference to certain contextual elements over others. These are activities with technological artifacts, models and simulations, service-learning activities, field trips, work in an appropriate space and the student’s presentation of their own results. These elements can be considered as a contextual basis for the cognitive development of pupils in general technology education. Teachers’ perception of the influence of other elements of the teaching context is not negligible, but obviously there is no priority over these elements, which is why further research is needed.